Pregnancy and Obstetrical Outcomes in Women Over 40 Years of Age - Dietl, A.; Cupisti, S.; Beckmann, M. W.; Schwab, M.; Zollner, U. (Geburtshilfe und Frauenheilkunde, 2015)
Introduction: Delayed childbearing is increasing, and advanced maternal age has been associated with an increased risk of obstetrical complications. The purpose of this study was to evaluate pregnancy outcomes in women with advanced maternal age (≥ 40 years). Methods: Maternal and obstetrical data were collected from the Department of Obstetrics and Gynecology of the University of Wuerzburg for the period from 2006 to 2011. In this retrospective analysis we compared the outcomes for women aged ≥ 40 years (n = 405) with those of three younger subgroups (I: < 30 y; II: 30–34 y; III: 35–39 y). Results: Pregnant women older than 40 years had more chronic diseases such as hypertension, needed medical treatment more frequently and had a higher thrombosis risk. Pregnancy-induced diseases such as gestational diabetes, preeclampsia and pregnancy-associated hypertension occurred more often in women ≥ 40 years of age. Compared to mothers who were younger than 30 years, primiparous women ≥ 40 years had a more than four times higher overall cesarean section rate and four times higher elective cesarean section rate. Furthermore, they required longer hospital stays, both after cesarean section and after vaginal delivery. The preterm birth rate (≤ 32 weeks of gestation) was similar across the different age groups. Conclusions: The outcomes of pregnancy and childbirth and for newborns born to women ≥ 40 years did not vary significantly from those of younger women if the following conditions were met: a) pre-existing chronic diseases were treated medically and dietetically; b) pregnancy-induced morbidity was monitored regularly and controlled medically; c) women attended regular prenatal check-ups; d) a healthy lifestyle was adhered to during pregnancy, and e) delivery occurred in a perinatal center.
Keywords: pregnancy; advanced maternal age; gestational diabetes; hypertension; cesarean section